Secondary Plant Metabolites LogP Determination: the Case of Boropinic and Geraniloxyferulic Acids - Epifanio, Isabella; Genovese, Salvatore; Carlucci, Giuseppe; Epifano, Francesco; Locatelli, Marcello (Current Bioactive Compounds, 2015)
Lipophilicity, expressed quantitatively through the LogP, is the most important physicochemical property for pharmacodynamic and pharmacokinetic characterization of the tested compound, as well as the most widely used parameter for quantitative structure-activity relationships (QSAR) descriptions. For this purpose three analytical techniques: the classical Shake Flask, the innovative Vortex-Assisted Liquid-Liquid Micro-Extraction (VALLME), and HPLC method, have been employed for the LogP determination of naturally occurring oxyprenylated secondary metabolites such as boropinic and geraniloxyferulic (GOFA) acid. These techniques have allowed us to correctly determine the LogP value for model molecule (ferulic acid) and from the comparison, by means of statistical techniques, of the obtained results it was possible to determine, not only for the first time, the LogP value of these secondary metabolites with interesting biological activity, but it was also possible to highlight the potential and limitations of the used techniques respect to the presence of interfering and / or degradation products.
Keywords: lipophilicity evaluation